On the theory of stability of motion of a nonlinear system on a time scale - Martynyuk-Chernienko, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate the problem of stability of a nonlinear system on a time scale and propose a unified approach to the analysis of stability of motion based on a generalized direct Lyapunov method.